2019
DOI: 10.3389/fpls.2019.00970
|View full text |Cite
|
Sign up to set email alerts
|

Plant Proteins and Processes Targeted by Parasitic Nematode Effectors

Abstract: Sedentary endoparasitic nematodes, such as root-knot nematodes (RKN; Meloidogyne spp.) and cyst nematodes (CN; Heterodera spp. and Globodera spp.) cause considerable damage to agricultural crops. RKN and CN spend most of their life cycle in plant roots, in which they induce the formation of multinucleate hypertrophied feeding cells, called “giant cells” and “syncytia,” respectively. The giant cells result from nuclear divisions of vascular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 104 publications
1
73
0
5
Order By: Relevance
“…Recent studies showed two PDI-like proteins of PPNs, MgPDI and HsPDI, were localized to the apoplast when GFP fusions were transiently expressed in N. benthamiana (Habash et al, 2017;Tian et al, 2019), indicating their different functional mechanism during nematode parasitism. Despite the hundreds of effectors characterized (Mejias et al, 2019), few RKN effectors have been demonstrated to be secreted in planta and to target giant cells. Example of effectors are the M. incognita Mi-EFF1 (Jaouannet et al, 2012) and MiMIF-2 (Zhao et al, 2019), the Meloidogyne javanica MjNULG1a (Lin et al, 2016) and the M. graminicola MgGPP (Chen et al, 2017) and Mg16820 (Naalden et al, 2018).…”
Section: Mipdi1 Is Secreted Throughout Parasitism and Targets The Giamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed two PDI-like proteins of PPNs, MgPDI and HsPDI, were localized to the apoplast when GFP fusions were transiently expressed in N. benthamiana (Habash et al, 2017;Tian et al, 2019), indicating their different functional mechanism during nematode parasitism. Despite the hundreds of effectors characterized (Mejias et al, 2019), few RKN effectors have been demonstrated to be secreted in planta and to target giant cells. Example of effectors are the M. incognita Mi-EFF1 (Jaouannet et al, 2012) and MiMIF-2 (Zhao et al, 2019), the Meloidogyne javanica MjNULG1a (Lin et al, 2016) and the M. graminicola MgGPP (Chen et al, 2017) and Mg16820 (Naalden et al, 2018).…”
Section: Mipdi1 Is Secreted Throughout Parasitism and Targets The Giamentioning
confidence: 99%
“…The precise localization of effectors and the identification of their host targets are essential for a better understanding of their biological functions. Only a few host target proteins of RKN effectors have been identified to date (Mejias et al, 2019). The M. incognita effector Mi16D10 has been shown to interact with Arabidopsis SCARECROW-like transcription factors (Huang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The GPCN juveniles penetrate plant roots in which they induce the formation of feeding syncytia. The effector proteins from oesophageal glands trigger the chain of metabolic and morphological changes resulting in fusion of several root cells into a feeding structure as well as suppression of plant immune response [18]. In a few investigations of plant varieties resistant to sedentary nematodes the revealed resistance mechanisms were mainly based on incompatible interaction and hypersensitive response: a zone of dead cells formed either at early or at later stages after infestation isolated juveniles from nutrient supply and prevented completion of their life cycle [19].…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports of insect or nematode effectors that directly target PRRs. However, these pests produce numerous effectors which suppress immunity through as yet unknown mechanisms (Hogenhout and Bos, 2011; Mejias et al, 2019), and nematodes are known to manipulate RKs in other signaling pathways through ligand mimicry (Hu and Hewezi, 2018). The identification of additional effectors and their activities is important both to better understand pathogen strategies and to further elucidate the proteins involved in immune signaling and their functions.…”
Section: Pathogen Effectors Targeting Prr Complexesmentioning
confidence: 99%